2006
DOI: 10.1037/0012-1649.42.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Contingency, imitation, and affect sharing: Foundations of infants' social awareness.

Abstract: Predictions about the role of contingency, imitation, and affect sharing in the development of social awareness were tested in infants during natural, imitative, and yoked conditions with their mothers at 5 and 13 weeks of age. Results showed that at both ages, infants of highly attuned mothers gazed, smiled, and vocalized positively more during the natural than during the imitative and yoked conditions, whereas they increased negative vocalizations during the yoked conditions. In contrast, infants of less att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 46 publications
3
87
0
3
Order By: Relevance
“…On a more perceptual level, the term contingency refers to a temporal sequence of behavior and reaction, and it has been shown that it plays an important role in the process of developmental learning (e.g., Kindermann, [116]; and Markova and Legerstee, [137]). In the literature, there is an agreement that contingency is an important factor in the cognitive development of infants-as researched, e.g., within the still face paradigm (e.g., Tronick et al, [252] and Muir and Lee, [150]).…”
Section: A Intermodal Learning: Contingency and Synchronymentioning
confidence: 99%
“…On a more perceptual level, the term contingency refers to a temporal sequence of behavior and reaction, and it has been shown that it plays an important role in the process of developmental learning (e.g., Kindermann, [116]; and Markova and Legerstee, [137]). In the literature, there is an agreement that contingency is an important factor in the cognitive development of infants-as researched, e.g., within the still face paradigm (e.g., Tronick et al, [252] and Muir and Lee, [150]).…”
Section: A Intermodal Learning: Contingency and Synchronymentioning
confidence: 99%
“…In both of these studies, mothers' positive affect may have served as a stronger stimulus of jealousy due to signaling the presence of a caregiver who is in greater possession of desired resources or, as Bradley (this volume, Chapter 10) suggests, this is a context that is more appealing due to being more obviously relational. The phenomenon also deserves closer attention toward understanding of fundamental capacities in the general area of social cognition and communicative acts, such as those involving intentionality, animicity, intersubjectivity, joint attention, and social referencing (Bauminger & Kasari, 2000;Boccia & Campos, 1989;Draghi-Lorenz et al, 2001;Flavell & Miller, 1998;Hobson, 2004;Markova & Legerstee, 2006), and also more specifically toward the goals of the present study, toward formulation of a basis for an interpretation of jealousy. In addition to its heightened presentation in the context of jealousy evocation, this interactive pattern is rather unique.…”
Section: Resultsmentioning
confidence: 99%
“…Distintos factores pueden haber propiciado dicha situación. Por un lado, en muchas investigaciones posteriores se ha tomado el término "entonamiento afectivo" como un modo de calificar globalmente el comportamiento materno o el segmento de interacción social completa como entonada o no-entonada (e.g., Bartling et al, 2010;Feldman & Greenbaum, 1997;Hrynchak & Fouts, 1998;Legerstee et al, 2007;Markova & Legerstee, 2006). En tales trabajos, el entonamiento afectivo se refiere a la calidad de atención y de reciprocidad establecida entre los participantes y se habla de la "sintonía afectiva lograda", utilizando esta expresión para calificar la "calidad" de la sensibilidad materna.…”
Section: Estudios Empíricos Sobre Entonamiento Afectivounclassified